Patterns of inheritance of the symptoms of Huntington's disease suggestive of an effect of genomic imprinting. - Ridley, R M (1991)
The interaction of symptomatology (rigidity/chorea) in Huntington's disease (HD) with age of onset (AO) was examined using data from the Research Roster for Huntington's Disease Patients and Families. It was shown that AO varies between families and between paternal and maternal transmission and that rigidity is associated specifically with very early onset, major anticipation, paternal transmission, and young parental AO. It is proposed that AO depends on the state of methylation of the HD locus, which varies as a familial trait, and as a consequence of 'genomic imprinting' determined by parental transmission. Young familial AO and paternal imprinting interact to produce, occasionally, a major change in gene expression, that is, the early onset/rigid variant.